The answer is <span>a=<span><span><span>√<span><span>x3</span><span>y5</span></span></span><span> or </span></span>a</span></span>=<span>−<span>√<span><span>x3</span><span>y<span>5</span></span></span></span></span>
We can use pythagorean theorem:
a^2 + b^2 = c^2
4 + 9 = c^2
13 = c^2
sqrt of 13 = c
Hope this helps!
Answer:
Step-by-step explanation:
1 : 3 : : 4: x
Multiply 1 and x and multiply 3 and 4
x = 12
Answer:
i need more info
Step-by-step explanation:
please comment on this to tell me all of said details
Answer:
(x-y)(x+6)
Step-by-step explanation:
x^2+6x-xy-6y
x*(x+6)-y(x+6)
(x-y)(x+6)